Der sowjetische Traum vom Fliegen Analyseversuch eines gesellschaftlichen Phaenomens - Kluge, Robert (Slavistische Beitraege, 1997)
It is not the anthropological-psychological level of the realized flight dream, not psychoanalysis and dream interpretation, which is the subject of this work, but the attempt to take stock and the impact of a massive propaganda tool as an integrating element in a totalitarian society.